Involvement of multiple myeloma cell-derived exosomes in osteoclast differentiation - Raimondi, Lavinia (Oncotarget, 2015)
Bone disease is the most frequent complication in multiple myeloma (MM) resulting in osteolytic lesions, bone pain, hypercalcemia and renal failure. In MM bone disease the perfect balance between bone-resorbing osteoclasts (OCs) and bone-forming osteoblasts (OBs) activity is lost in favour of OCs, thus resulting in skeletal disorders. Since exosomes have been described for their functional role in cancer progression, we here investigate whether MM cell-derived exosomes may be involved in OCs differentiation. We show that MM cells produce exosomes which are actively internalized by Raw264.7 cell line, a cellular model of osteoclast formation. MM cell-derived exosomes positively modulate pre-osteoclast migration, through the increasing of CXCR4 expression and trigger a survival pathway. MM cell-derived exosomes play a significant pro-differentiative role in murine Raw264.7 cells and human primary osteoclasts, inducing the expression of osteoclast markers such as Cathepsin K (CTSK), Matrix Metalloproteinases 9 (MMP9) and Tartrate-resistant Acid Phosphatase (TRAP). Pre-osteoclast treated with MM cell-derived exosomes differentiate in multinuclear OCs able to excavate authentic resorption lacunae. Similar results were obtained with exosomes derived from MM patient's sera. Our data indicate that MM-exosomes modulate OCs function and differentiation. Further studies are needed to identify the OCs activating factors transported by MM cell-derived exosomes.